Analisis Agresi Verbal Pengguna Media Sosial Ditinjau dari Identitas Peran Gender pada Mahasiswa - Setyoningsih, Yunita Dwi; Srianturi, Yanuari (Pusat Kajian Bimbingan dan Konseling FIPPS Unindra, 2024)
Technological developments shift social relations with communication into cyberspace. The negative elements in the virtual communication pattern raise counter comments to the values that students have. This study aims to describe the verbal aggression of social media users in terms of gender role identity in college students. Data analysis techniques using quantitative descriptive with technical proportions. Method of collecting data; verbal aggression scale, observation, interviews and found the overall level of Verbal Aggression of social media users is in the high category of 10 students by 5% of 199 respondents; the medium category is 50 students by 25% of 199 respondents and the low category is 139 students by 70% of 199 respondents from the verbal aggression of male and female student social media users. The most common form of verbal aggression by students on social media is direct active verbal aggression, namely 31% in the form of cursing, insulting, insulting, threatening on social media. This study recommends counseling services to reduce verbal aggression on social media.